REDESIGN GEOMETRIK JALAN PADA RUAS JALAN RAYA SALOPA DESA KAWITAN KABUPATEN TASIKMALAYA (STA 0+000 - 0+750) - Saleh, Rachman; Saepudin, Uu; Martha, Taufik (Jurnal Ilmiah Teknik Sipil, 2026)
Road geometry is the planning of the physical form of a road, taking into account technical, economic, and environmental aspects to ensure the safety and comfort of users. Kawitan Village Road, Kecamatan Salopa, faces various problems, such as damaged road conditions, steep slopes, curves, and the absence of shoulders and road markings, all of which have the potential to cause accidents. Redesign is a solution to these geometric problems, aiming to improve and enhance the road’s condition. This study aims to redesign the geometric road and determine the horizontal and vertical alignment on the Salopa highway section of Kawitan Village, Tasikmalaya Regency, by using quantitative research to obtain primary data and Tata Cara Perencanaan Geometrik Jalan Antar Kota Tahun 1997 and the 2011 AASTHO reference for secondary data. The benefits of this study can provide technical solutions for improving road geometric conditions, as well as being a reference for practitioners in road geometric design. The results of the study show that the Salopa highway section of Kawitan Village, Tasikmalaya Regency has a design speed of 40 km/hour, a road length of 514.81 m, a road function Kolektor III B, a road type of 2/2 – TT. The horizontal alignment produces 3 SCS type curves with each angle and radius of 67.93˚ and 241 m, 110.191˚ and 99 m and 31.472˚ and 178 m. While the vertical alignment produces 3 convex curves with LV design values of 50 m, 25 m and 102 m and 3 concave curves with LV design values of 8 m, 32 m and 45 m.